Analisis Kualitas Penerapan Good Corporate Governace pada Bank Sulselbar Cabang Syariah Makassar - Rezki Astuti Soraya (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2022)
Good Corporate Governance in Islamic banking is considered important because Islamic banking is currently showing a fairly rapid development. It is necessary to emphasize how the real governance that must be applied by Islamic banking is. This is very important, because Islamic banking is philosophically and substantially different from conventional banking. This study aims to find out about the quality of the implementation of Good Corporate Governance at Bank Sulselbar Syariah Makassar Branch. This study uses qualitative methods and uses data analysis techniques with a critical alternative perspective. Data collection techniques used are interviews and documentation. The results showed that the Good Corporate Governance of Bank Sulselbar Syariah Makassar Branch, although in good quality, still showed some weaknesses that still needed to be improved.